2015
DOI: 10.1111/1440-1681.12383
|View full text |Cite
|
Sign up to set email alerts
|

Preserved cardiac mitochondrial function and reduced ischaemia/reperfusion injury afforded by chronic continuous hypoxia: Role of opioid receptors

Abstract: Chronic continuous normobaric hypoxia (CNH) increases cardiac tolerance to acute ischaemia/reperfusion injury. The objective of this study was to find out whether the cardioprotective effect of CNH mediated by opioid receptors is associated with preservation of mitochondrial function. Rats were adapted to CNH (12% oxygen) for 3 weeks. Isolated perfused hearts were subjected to 45 min of global ischaemia and 30 min of reperfusion; subgroups were pretreated with non-selective opioid receptor antagonist naloxone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Our studies and those of others indicate that an adaptation to intermittent hypoxia (AIH) provides increased cardiac tolerance to ischemia and reperfusion (Neckar et al 2002;Kolar et al 2005;Naryzhnaya et al 2009;Estrada et al 2016;Míčová et al 2017). The number of publications devoted to the cardioprotective effect of continuous chronic normobaric hypoxia is also large (Tajima et al 1994;Maslov et al 2013Maslov et al , 2015Alanova et al 2015Alanova et al , 2017Holzerova et al 2015;Kasparova et al 2015;Naryzhnaya et al 2015;Kolar et al 2017;Neckář et al 2017). Some studies suggest that the adaptation of rats to chronic continuous normobaric hypoxia (CCNH) reduces tolerance of heart to the action of hypoxia/reoxygenation and allows for increasing cardiac resistance to ischemia and reperfusion and represents only adaptation to AIH (Milano et al 2002(Milano et al , 2004(Milano et al , 2010(Milano et al , 2011.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our studies and those of others indicate that an adaptation to intermittent hypoxia (AIH) provides increased cardiac tolerance to ischemia and reperfusion (Neckar et al 2002;Kolar et al 2005;Naryzhnaya et al 2009;Estrada et al 2016;Míčová et al 2017). The number of publications devoted to the cardioprotective effect of continuous chronic normobaric hypoxia is also large (Tajima et al 1994;Maslov et al 2013Maslov et al , 2015Alanova et al 2015Alanova et al , 2017Holzerova et al 2015;Kasparova et al 2015;Naryzhnaya et al 2015;Kolar et al 2017;Neckář et al 2017). Some studies suggest that the adaptation of rats to chronic continuous normobaric hypoxia (CCNH) reduces tolerance of heart to the action of hypoxia/reoxygenation and allows for increasing cardiac resistance to ischemia and reperfusion and represents only adaptation to AIH (Milano et al 2002(Milano et al , 2004(Milano et al , 2010(Milano et al , 2011.…”
Section: Introductionsupporting
confidence: 54%
“…The results of our experiments with atractyloside were somewhat unexpected since we had previously demonstrated that adaptation to chronic continuous hypoxia blocks the opening of MPT pore in response to ischemia/reperfusion of the isolated rat heart (Maslov et al 2015). It has been shown that atractyloside abolished infarct reducing effect chronic intermittent hypoxia (Bu et al 2015).…”
Section: Disscussionmentioning
confidence: 55%
“…Since DOR is widely distributed in the central and peripheral systems including the heart and kidney [41, 44, 49], an intravenous ligand may elicit systemic effects through many complex and varied mechanisms. The change in survival time may have resulted from the diverse effects of opioid ligands on various organs and organ systems, especially in the heart and kidney [64-71]. …”
Section: Opioid Receptors and Neuroprotection: Major Controversies Inmentioning
confidence: 99%
“…Importantly, it has been established that the infarct size-limiting effect of CNH is mediated by activation of opioid receptors (OR), particularly δ 2 and μ subtypes (Maslov et al 2013). We have shown earlier that these OR also play a role in CNH-induced protection of the isolated perfused rat heart against ischemia and reperfusion (Maslov et al 2015). Therefore, it can be argued that OR, which provide an adaptive increase in heart tolerance to the impact of ischemia and reperfusion, are localized in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is reason to presume that intracellular oxygen sensor prolyl-4-hydroxylase (Semenza 2014), reactive oxygen species (Szarszoi et al 2003), NO synthase (Alanova et al 2015, Zaobornyj et al 2009, protein kinase C (Hlavackova et al 2010), p38 MAP kinase (Milano et al 2010, Ravingerova et al 2007, and AMP-activated protein kinase (Sukhodub et al 2007) participate in the mechanism of cardioprotection at chronic hypoxia. As a result of the work of these signaling pathways, transcription factors such as HIF-1α, NFκB and AP-1 are activated (Semenza 2009), and changes in the functioning of mitochondrial ion channels and mPTP lead to improved energy metabolism of mitochondria (Maslov et al 2015) and their resistance to ischemia/reperfusion. Importantly, it has been established that the infarct size-limiting effect of CNH is mediated by activation of opioid receptors (OR), particularly δ 2 and μ subtypes (Maslov et al 2013).…”
Section: Introductionmentioning
confidence: 99%